2024
DOI: 10.1093/eurheartj/ehae080
|View full text |Cite
|
Sign up to set email alerts
|

Kidney replacement therapy: trends in incidence, treatment, and outcomes of myocardial infarction and stroke in a nationwide Scottish study

Peter J Gallacher,
David Yeung,
Samira Bell
et al.

Abstract: Background and Aims Patients with kidney failure have a higher risk of cardiovascular disease compared with the general population. Whilst temporal trends of myocardial infarction and stroke are declining in the general population, these have not been evaluated in patients with kidney failure. This study aimed to describe national trends in the incidence, treatment, and outcomes of myocardial infarction and stroke in patients with kidney failure (i.e. on dialysis or with a kidney transplant) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The major concern for all patients with AF is the increased risk of embolic stroke, and this also applies to HD patients. A recently published Scottish study showed that in patients receiving kidney replacement therapy between January 1996 and December 2016, the incidence of stroke was 2- to 4-fold higher compared with the general population and was associated with a poor prognosis [ 7 ]. A more than doubled prevalence of stroke (5.2 versus 1.9 events/100 patients/year) [ 3 ] and an adjusted odds ratio (OR) of 1.5 for new-onset cerebral infarction were demonstrated in CKD G5D patients with AF [ 8 ] compared with patients without AF.…”
Section: Introductionmentioning
confidence: 99%
“…The major concern for all patients with AF is the increased risk of embolic stroke, and this also applies to HD patients. A recently published Scottish study showed that in patients receiving kidney replacement therapy between January 1996 and December 2016, the incidence of stroke was 2- to 4-fold higher compared with the general population and was associated with a poor prognosis [ 7 ]. A more than doubled prevalence of stroke (5.2 versus 1.9 events/100 patients/year) [ 3 ] and an adjusted odds ratio (OR) of 1.5 for new-onset cerebral infarction were demonstrated in CKD G5D patients with AF [ 8 ] compared with patients without AF.…”
Section: Introductionmentioning
confidence: 99%